Developing a Tourism Innovation Typology: Leveraging Liminal Insights. (July 2014) - Brooker, Ed; Joppe, Marion
Innovation has become a buzzword, regularly cited to convey any improvement made, regardless of the extent of newness. Tourism innovation has historically been viewed as either incremental or radical, a binary developed within manufacturing. However, given that incremental improvements are the norm in the tourism sector and that radical innovation is an abnormality, the binary is not representative of tourism innovation. We suggest a three-level typology, based on field research in Europe and Australia, and informed by Rogers's innovation diffusion model; the concept of liminality and its role in the search for tacit knowledge through weak network ties; and the need to ask ultimate (why) rather than proximate (what, how) questions. Since the term innovation is overused, we introduce three alternate concepts: the "artist, " who is comparable to the innovator; the "artisan, " who represents early innovation adopters; and the "painter, " who epitomizes the early and late majority.